2012
DOI: 10.3103/s1068375512050134
|View full text |Cite
|
Sign up to set email alerts
|

Cu/Co-W nanolayers electrodeposited from single bath and investigations of their nanohardness

Abstract: For the first time thick (~8 μm) Cu/Co-W multilayered coatings with individual layers ranging from 5 to 200 nm were electrodeposited from a single bath. The content of tungsten in rich in CoW layers was controlled by varying current densities in a citrate borate bath. Continuous Multi Cycle (CMC) nanoin dentation technique was used to analyze mechanical properties of those deposits. Optical examination of the indented zone revealed the absence of cracks inside and outside the indentation area in the interval o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
2
0
0
Order By: Relevance
“…This is due to maximum incorporation of hard tungsten carbide nano particles at current density of 60 mA/cm 2 . The hardness improvement from 110 HV (pure Cu) to 530 HV (Cu-Co/WC)) is comparable with the results reported by Tsyntsaru et al [8]. It is also observed that Cu-Co/WC nano-composite coating has a much higher micro-hardness value (530 HV) than that of the Cu/WC nano-composite coating [9].…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…This is due to maximum incorporation of hard tungsten carbide nano particles at current density of 60 mA/cm 2 . The hardness improvement from 110 HV (pure Cu) to 530 HV (Cu-Co/WC)) is comparable with the results reported by Tsyntsaru et al [8]. It is also observed that Cu-Co/WC nano-composite coating has a much higher micro-hardness value (530 HV) than that of the Cu/WC nano-composite coating [9].…”
Section: Resultssupporting
confidence: 79%
“…Beyond this current density value, the amount of co-deposited tungsten carbide particles decreases. Before reaching the maximum, the increment can be attributed to the increased tendency for absorbed particles to be attached to the cathode surface, which is consistent with Guglielmi's model [8]. When current density is higher than 60 mA/cm 2 , the decreasing trend can be explained by the fact that an increase in current density results in more rapid deposition of the metal matrix and fewer ceramic particles could be embedded in the coating.…”
Section: Resultssupporting
confidence: 75%